Thiosulfate sulfurtransferase prevents hyperglycemic damage to the zebrafish pronephros in an experimental model for diabetes - Al-Dahmani, Zayana M.; Li, Xiaogang; Wiggenhauser, Lucas; Ott, Hannes; Kruithof, Paul D.; Lunev, Sergey; A. Batista, Fernando; Luo, Yang; Dolga, Amalia M.; Morton, Nicholas M.; Groves, Matthew R.; Kroll, Jens; et al. (Scientific reports, 2022)
Thiosulfate sulfurtransferase (TST, EC 2.8.1.1), also known as Rhodanese, was initially discovered as a cyanide detoxification enzyme. However, it was recently also found to be a genetic predictor of resistance to obesity-related type 2 diabetes. Diabetes type 2 is characterized by progressive loss of adequate β-cell insulin secretion and onset of insulin resistance with increased insulin demand, which contributes to the development of hyperglycemia. Diabetic complications have been replicated in adult hyperglycemic zebrafish, including retinopathy, nephropathy, impaired wound healing, metabolic memory, and sensory axonal degeneration. Pancreatic and duodenal homeobox 1 (Pdx1) is a key component in pancreas development and mature beta cell function and survival. Pdx1 knockdown or knockout in zebrafish induces hyperglycemia and is accompanied by organ alterations similar to clinical diabetic retinopathy and diabetic nephropathy. Here we show that pdx1-knockdown zebrafish embryos and larvae survived after incubation with thiosulfate and no obvious morphological alterations were observed. Importantly, incubation with hTST and thiosulfate rescued the hyperglycemic phenotype in pdx1-knockdown zebrafish pronephros. Activation of the mitochondrial TST pathway might be a promising option for therapeutic intervention in diabetes and its organ complications.
Gesehen am 07.11.2023